Determinants of dividend policy in industrial firms in Malaysia / Hanis Md Shaari - Md Shaari, Hanis (Faculty of Business Management, 2017)
The function of the paper is to find out the factors that contributed to the determinant of dividend policy for the industrial companies. The data that will be examined in this study will retrieve from UiTM Data Stream. The sample for this paper will consist of 30 industrial companies which are listed from the Board of Bursa from the year 2011 to 2015. The method for analyses the data in this project is Multiple Linear Regression with panel data. In this paper, the dependent variable is dividend payout ratio while for the independent variables is profitability, leverage and operating activities. Based on the variables, the objectives of the study is to determine the effect of profitability (ROE), leverage (TIE, DR, and WCR) and operating activities (tangibility and firm‟s size) to the industrial companies‟ dividend policy. In conclusion, the result of this research will help the investor to make a systematic strategy and make an appropriate decision in choosing a company based in the company dividend policy.